Total and partial IgA deficiency in blood serum in children. Clinical observation - T. B. Pavlova; V. M. Shinkareva (Acta Biomedica Scientifica)
We conducted a 13-year observation of 9 patients with total and partial IgA deficiency. The age of children in primary treatment was 3.0 ± 0.2 years on average. The observation was carried out on the basis of the outpatient service of Irkutsk State Regional Children's Clinical Hospital. The examination included immunological, clinical-allergic and functional methods of research. To assess the humoral link of the immune system, serum Ig concentrations of classes A, M, G (mg/dl) were determined in the first 3 years annually, and then every 2-3 years. As a result, it was found that among the patients with IgA immunodeficiency, boys predominate over girls in a ratio of 3.5:1. With a partial IgA deficiency detected at an early age, the majority of patients have normalization of their IgA level, but sometimes there is a transformation into a selective IgA deficiency with an increase in the number of clinical markers of this condition. With a selective deficiency of IgA detected at an early age, half of the patients have normalization of the IgA level by the age of adolescence, but another half still maintain a significant decrease in serum IgA. Clinical manifestations in the majority of observed children with selective IgA deficiency included atopic respiratory diseases - bronchial asthma and allergic rhinitis, in one case - diabetes mellitus. In some children, the selective deficiency of IgA was asymptomatic.